Pelaksanaan Supervisi Akademik Pengawas dalam Pembinaan Guru PAI Pada Madrasah Aliyah Pondok Pesantren Nurul Falah - Tonta, Norma; Siraj, Arifuddin; Yaumi, Muhammad (Universitas Muhammadiyah Surakarta, 2019)
This research aims to describe the implantation of academic supervision of supervisors in the development of Islamic Religious education teachers at Madrasah Aliyah Pondok Pesantren Nurul Falah of Bulukumba Regency. This research is a qualitative research with the phenomenology approach. The subject of this study is the supervisors, head of Madrasah, teachers, and students at Madrasah Aliyah Nurul Falah. The data collection techniques used are observation, interview, and documentation. Processing techniques and data analysis through data reduction, data display, and verification or withdrawal of conclusions. The results showed that the implementation of academic supervision of supervisors at Madrasah Aliyah Pondok Pesantren Nurul Falah of Bulukumba Regency from the planning aspect, monitoring program has been included either because the supervisor has done the planning before conducting supervision activities by making agreement with the madrasah personnel to be supervised so as to prepare. However, the teacher's aspect of coaching has not been well-running so much of the assessment aspect. Thus, the results of the implementation of the academic supervision of supervisors in the development of Islamic Religious education teachers at Madrasah Aliyah Pondok Pesantren Nurul Falah of Bulukumba Regency is not optimal so it still needs to be improved, especially on the aspect of development and judgment.